Linking Procurement Planning and Tendering to Service Delivery Performance: Evidence from Public Sector Supply Chain Systems - Okebechi, Gbeyongu Victoria; Ahemen, Member; Tyokosu , Simon (Journal of Supply Chain and Entrepreneurship, 2026)
Background: Public sector procurement has evolved into a strategic component of supply chain management, yet many higher education institutions continue to face inefficiencies in translating procurement processes into effective service delivery. While prior studies emphasize transparency and compliance, limited empirical evidence explains how specific procurement mechanisms—particularly planning and tendering—shape service delivery performance within institutional supply chain systems. Aims: This study aims to examine the linkage between procurement planning and tendering practices and service delivery performance, positioning procurement as a critical driver of public sector supply chain effectiveness. Methods: A quantitative survey design was employed, drawing data from 95 procurement-related personnel in a public university setting. Data were collected using a structured questionnaire with validated reliability (Cronbach’s alpha = 0.86). Descriptive statistics (mean and standard deviation) were used to assess response patterns, whileSpearman rank-order correlation was applied to test the relationships between procurement planning, tendering, and service delivery performance. Result: The findings reveal that procurement planning demonstrates a statistically significant positive relationship with service delivery performance (ρ = 0.327, p < 0.05), indicating that structured planning enhances operational efficiency and alignment of resources. Similarly, tendering exhibits a stronger significant relationship (ρ = 0.482, p < 0.05), suggesting that transparent and competitive supplier selection processes play a pivotal role in improving service outcomes. The overall results highlight procurement as an embedded mechanism within public sector supply chains that directly influences performance. Conclusion: This study confirms that procurement planning and tendering are not merely administrative functions but constitute core operational mechanisms that shape service delivery performance within public sector supply chain systems. By reframing procurement through a supply chain perspective, the study contributes to bridging the gap between procedural compliance and performance-oriented outcomes. The findings underscore the importance of integrating structured planning, transparent tendering, and professional capacity development to enhance efficiency and accountability in public institutions. Furthermore, the study provides empirical support for positioning procurement as a strategic lever for value creation, offering practical insights for policymakers and institutional managers seeking to strengthen governance and service quality in resource-constrained environments